2009
DOI: 10.1002/ange.200901226
|View full text |Cite
|
Sign up to set email alerts
|

9,10‐Dihydro‐9,10‐diboraanthracene: Supramolecular Structure and Use as a Building Block for Luminescent Conjugated Polymers

Abstract: Dreizentren‐Zweielektronen‐B‐H‐B‐Brücken kennzeichnen die neuartige polymere Struktur der Titelverbindung im Festkörper. Dieses Organoboran dient als effiziente Vorstufe für die Herstellung bordotierter π‐konjugierter Polymere durch Hydroborierungspolymerisation mit einem funktionalisierten 1,4‐Diethinylbenzol (siehe Bild). Diese Polymere bilden dünne Filme, die sich durch intensive grüne Lumineszenz auszeichnen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 77 publications
(24 citation statements)
references
References 38 publications
1
21
0
2
Order By: Relevance
“…The dimer is held together by two central B-H-B two-electron-three-center bonds. The resulting interdimer B2···B2# distance is 1.817 (2) , which compares well with the respective intermonomer B···B distances in polymeric DBA ((DBA) n ; Figure 3, bottom; average value: 1.818(12) [64] ). Furthermore, similar to (DBA) n , the monomeric units of compound (7) 2 deviate significantly from planarity with a dihedral angle of 135.88 between the two phenylene rings (cf.…”
Section: Reactivity Of 12-c 6 H 4 a C H T U N G T R E N N U N G (Bh supporting
confidence: 63%
See 2 more Smart Citations
“…The dimer is held together by two central B-H-B two-electron-three-center bonds. The resulting interdimer B2···B2# distance is 1.817 (2) , which compares well with the respective intermonomer B···B distances in polymeric DBA ((DBA) n ; Figure 3, bottom; average value: 1.818(12) [64] ). Furthermore, similar to (DBA) n , the monomeric units of compound (7) 2 deviate significantly from planarity with a dihedral angle of 135.88 between the two phenylene rings (cf.…”
Section: Reactivity Of 12-c 6 H 4 a C H T U N G T R E N N U N G (Bh supporting
confidence: 63%
“…It has been suggested that monomer-folding in (DBA) n is the result of otherwise-unfavorable steric interactions between adjacent DBA moieties and the same reasoning is probably true for compound (7) 2 . [64,65] Compound (7) 2 features B1 À S1 bond lengths of 1.997 (1) , which are somewhat shorter than in the corresponding syn-diadduct of DBA, that is,…”
Section: Reactivity Of 12-c 6 H 4 a C H T U N G T R E N N U N G (Bh mentioning
confidence: 97%
See 1 more Smart Citation
“…Das 9,10‐Dihydro‐9,10‐diboranthracen (28) zeigt im Festkörper eine supramolekulare Struktur über Hydridbrücken analog zum Diboran. Hydroborierung mit geeigneten Diethinylbenzolen liefert grünlumineszierende konjugierte Polymere (29) 1_65…”
Section: Konjugierte Materialienunclassified
“…Compound 1 is the key starting material for the synthesis of (i) (phenyl) [2-(trimethylsilyl)phenyl]iodonium triflate (A; Scheme 1), one of the most efficient benzyne precursors available to date, [4,5] (ii) 9,10-dihydro-9,10-diboraanthracene (B; Scheme 1), a versatile building block of luminescent boron-doped p-conjugated polymers, [6,7] and (iii) 9,10-dimethyl-9,10-dihydro-9,10-diboraanthracene, a powerful ditopic LewisScheme 1. 1,2-Bis(trimethylsilyl)benzene (1) is a key starting material for the preparation of the benzyne precursor A, the polymer building block B, and Lewis-acid catalysts C. (i) cf.…”
Section: Introductionmentioning
confidence: 99%